Multiple surface wetting events in the greater Meridiani Planum region, Mars: Evidence from valley networks within ancient cratered highlands. Issue 4 (22nd February 2017) - Williams, R. M. E.; Chuang, F. C.; Berman, D. C.
Abstract: Morphological characterization of valley networks in three exposures of ancient cratered highlands (Nhc1 ) in the greater Meridiani Planum region yields insight into the Martian aqueous history. From our mapping, key regional differences are apparent in fine‐scale valley network attributes including morphologic type, planimetric form, density, and links to candidate paleolakes. This information, combined with crater retention age (inferred exposure age), provides new details on the relative timing and nature of aqueous processes in the region. Newly identified pitted‐type valley networks have morphological similarity to terrestrial pitted landforms in an evaporite setting. We interpret the pitted valley networks to reflect late‐stage groundwater processes concentrated along the former fluvial conduits. Evidence from this study indicates that localized reactivation of valley networks occurred during or after exhumation of eastern Nhc1 unit. Key Points: Mapped morphologic types of valley networks near Meridiani Planum, Mars, include channel, ridge, knob, and newly described pitted types Fine‐scale valley networks in the study region share similar attributes with dissolution landforms in Chilean Atacama Desert Localized reactivation of Martian valley networks via groundwater processes occurred during or after exhumation of eastern Nhc1 unit